Lesson Study Sebagai Sarana Meningkatkan Kualitas Dan Profesionalitas Pembelajaran - Nanang Nuryanta (Millah: Journal of Religious Studies, 2015)
Several factors can affect the learning process, that are teachers, learners, means, tools and media available and environment. Although that influence the success of learning a lot but can not be denied that teacher is the main factor and decisive for the success of the learning process. Teacher or educator professional will be able ensure learning process to be good. However, some facts indicate that many teachers teach and make the learning process as simply “just obligations”, they do not realize that the teacher is a profession who demands professionalism in practice. Therefore the need to model a new approach in coaching teachers, one of them with Lesson Study, namely learning model teachers will be able to be effectively implemented in educational institutions on the condition that there is a shared commitment to strong from the teachers themselves, school principals and the Education Department is supported by involvement of education experts. Lesson Study is not one learning model teaching profession only, therefore, needs to be combined with other models.